Biochemical and Histochemical Study on the Hypothalamus at Some Periods of Starvation and Refeeding After Starvation - TEMUR, A.; ATLI, M.; KARADAG, H.; DONMEZ, H.H.; ASKEROV, F. (Asian Journal of Chemistry, 2010)
This study was carried out to determine biochemical and histochemical alterations in the lateral (feeding centre) and ventro-medial (satiety centre) nuclei of hypothalamus in rats starved and refed after some periods of starvation. 180 Wistar albino rats were used in the investigation. The rats were starved for a periods of 1, 3, 5 and 7 d. The rats starved 5 d were refed for a periods of 5, 10, 15 and 30 d. The activity of the neutral peptide hydrolase was biochemically determined in the hypothalamus. In addition, histochemical investigation was made in the feeding and satiety centres. It was observed that the activity of the neutral peptide hydrolase became closer to the levels of the control group at 30th d of refeeding after 5 d starvation. It was concluded that the feeding centre was more sensitive to starvation than the satiety centre and the satiety centre was restored earlier than the feeding centre.